Serial tissue Doppler imaging in the evaluation of bronchopulmonary dysplasia-associated pulmonary hypertension among extremely preterm infants: a prospective observational study - Krishna Revanna Gopagondanahalli; Krishna Revanna Gopagondanahalli; Krishna Revanna Gopagondanahalli; Krishna Revanna Gopagondanahalli; Abdul Alim Abdul Haium; Abdul Alim Abdul Haium; Abdul Alim Abdul Haium; Abdul Alim Abdul Haium; Shrenik Jitendrakumar Vora; Shrenik Jitendrakumar Vora; Shrenik Jitendrakumar Vora; Shrenik Jitendrakumar Vora; et al. (Frontiers Media S.A., 2024)
ObjectivesTo evaluate serial tissue Doppler cardiac imaging (TDI) in the evolution of bronchopulmonary dysplasia-associated pulmonary hypertension (BPD-PH) among extremely preterm infants.DesignProspective observational study.SettingSingle-center, tertiary-level neonatal intensive care unit.PatientsInfant born <28 weeks gestation.Main outcome measuresUtility of TDI in the early diagnosis and prediction of BPD-PH and optimal timing for screening of BPD-PH.ResultsA total of 79 infants were included. Of them, 17 (23%) had BPD-PH. The mean gestational age was 25.9 ± 1.1 weeks, and mean birth weight was 830 ± 174 g. The BPD-PH group had a high incidence of hemodynamically significant patent ductus arteriosus (83% vs. 56%, p < 0.018), longer oxygen days (96.16 ± 68.09 vs. 59.35 ± 52.1, p < 0.008), and prolonged hospital stay (133.8 ± 45.9 vs. 106.5 ± 37.9 days, p < 0.005). The left ventricular eccentricity index (0.99 ± 0.1 vs. 1.1 ± 0.7, p < 0.01) and the ratio of acceleration time to right ventricular ejection time showed a statistically significant trend from 33 weeks (0.24 ± 0.05 vs. 0.28 ± 0.05, p < 0.05). At 33 weeks, the BPD-PH group showed prolonged isovolumetric contraction time (27.84 ± 5.5 vs. 22.77 ± 4, p < 0.001), prolonged isovolumetric relaxation time (40.3 ± 7.1 vs. 34.9 ± 5.3, p < 0.003), and abnormal myocardial performance index (0.39 ± 0.05 vs. 0.32 ± 0.03, p < 0.001). These differences persisted at 36 weeks after conceptional gestational age.ConclusionsTDI parameters are sensitive in the early evolution of BPD-PH. Diagnostic accuracy can be increased by combining the TDI parameters with conventional echocardiographic parameters. BPD-PH can be recognizable as early as 33-34 weeks of gestation.